Evaluation of attractive interactions in the second coordination sphere of iron complexes containing pendant amines. Issue 15 (18th March 2019) - Liao, Qian; Liu, Tianbiao; Johnson, Samantha I.; Klug, Christina M.; Wiedner, Eric S.; Morris Bullock, R.; DuBois, Daniel L.
Abstract : The ability of different ligands to attract a pendant amine is studied in a series of iron complexes. Abstract : The interactions between pendant amines in the second coordination sphere and ligands in the first coordination sphere are important for understanding the structures and reactivity of complexes containing P R 2 N R′ 2 ligands, which have been shown to be highly active H2 oxidation/production catalysts. A series of [Fe(P Ph 2 N Bn 2 )2 (X)(Y)] n + complexes have been prepared and structurally characterized. These complexes have two different ligands with which the pendant amines of the diphosphine ligand can interact. The solid state structure of cis -Fe(P Ph 2 N Bn 2 )2 Cl2 reveals that the six-membered rings adjacent to the P atoms are in a boat confirmation, resulting in close N⋯P distances that suggests the P atoms have a greater affinity for the lone pair of electrons on the N atom than chloride ligands. Similarly, boat conformations are observed for both rings adjacent to the hydride ligands of trans -[HFe(P Ph 2 N Bn 2 )2 (CH3 CN)] + and trans -HFe(P Ph 2 N Bn 2 )2 Cl, resulting in short N⋯H distances. Spectroscopic and computational studies of trans -[HFe(P Ph 2 N Bn 2 )2 (CO)] +, trans -[HFe(P Ph 2 N Bn 2 )(P Ph 2 N Bn 2 H)(CO)] 2+, and trans -[HFe(P Ph 2 N Bn 2 )2 (H2 )] + indicate the complexes are more stable when the pendant amines in boat conformations are adjacent to the hydride ligand. These data suggest an attractor ordering of H − > CO > H2 > PR3 > Cl − ∼ CH3 CN.